2010
DOI: 10.4067/s0716-10182010000100011
|View full text |Cite
|
Sign up to set email alerts
|

Prevalencia, factores de riesgo y manejo de la depresión en pacientes con infección por VIH: Revisión de la literatura

Abstract: Depression is one of the main psychiatric co-morbidities in HIV infection, presenting with a significantly higher prevalence than in the general population (around 35%). Its presence has been associated with poor quality of life, HIV disease progression and poor adherence to antiretroviral therapy. Although antidepressive treatment has demonstrated effectiveness on the management of depressive symptoms, improvement of clinical and laboratory parameters, and enhancement of antiretroviral adherence, depression i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
1
7

Year Published

2013
2013
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 49 publications
(159 reference statements)
0
6
1
7
Order By: Relevance
“…This contrasts with previous studies in outpatient PLWH, where depression has been shown to be more frequent (Bayon et al, 2012;Berger-Greenstein et al, 2007;Elliott, 2003;Nogueira Campos et al, 2006;Salters et al, 2016;Wolff et al, 2010); it could be explained due to time since HIV diagnosis of our sample, depression is more frequent after diagnosis. Women in our study not only showed higher vulnerability due to mental health issues, but also had social and economic vulnerability.…”
Section: Discussioncontrasting
confidence: 55%
See 1 more Smart Citation
“…This contrasts with previous studies in outpatient PLWH, where depression has been shown to be more frequent (Bayon et al, 2012;Berger-Greenstein et al, 2007;Elliott, 2003;Nogueira Campos et al, 2006;Salters et al, 2016;Wolff et al, 2010); it could be explained due to time since HIV diagnosis of our sample, depression is more frequent after diagnosis. Women in our study not only showed higher vulnerability due to mental health issues, but also had social and economic vulnerability.…”
Section: Discussioncontrasting
confidence: 55%
“…Our results are in line with international studies showing that affective and anxiety disorders are the most common psychiatric comorbidities related to HIV-AIDS (Salters et al, 2016). Depression and anxiety rates in PLWH range between 20% and 70% (Berger-Greenstein et al, 2007;Elliott, 2003;Nogueira Campos et al, 2006) and 10% to 40%, respectively (Bayon et al, 2012;Wolff, Alvarado & Wolff, 2010). Estimated prevalence varies widely due to differences in the measurements used and in the sociodemographic profiles of the populations evaluated (Moore et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Se estudiaron estas variables desde un enfoque de riesgo, de acuerdo al cual se hace necesario conocer la presencia de co-morbilidad y problemas psicológicos que obstaculizan el éxito de la TARV y disminuyen la calidad de vida de los pacientes. Además, se caracterizaron algunos factores psicosociales de pacientes adherentes y no adherentes 5,12 .…”
Section: Introductionunclassified
“…Además del factor biológico, se debe poner énfasis en otros componentes asociados y posibles desencadenantes de este trastorno ya que la depresión es el resultado de interacciones complejas entre factores sociales, psicológicos y biológicos que influencian el desarrollo, tratamiento y pronóstico de la enfermedad 6 .…”
Section: Factores De Riesgounclassified